The DanCavas Pilot Study of Multifaceted Screening for Subclinical Cardiovascular Disease in Men and Women Aged 65–74 Years. (January 2017) - Kvist, T.V.; Lindholt, J.S.; Rasmussen, L.M.; Søgaard, R.; Lambrechtsen, J.; Steffensen, F.H.; Frost, L.; Olsen, M.H.; Mickley, H.; Hallas, J.; Urbonaviciene, G.; Busk, M.; et al.
Abstract : Objective/Background: This pilot study of a large population based randomised screening trial investigated feasibility, acceptability, and relevance (prevalence of clinical and subclinical cardiovascular disease [CVD] and proportion receiving insufficient prevention) of a multifaceted screening for CVD. Methods: In total, 2060 randomly selected Danish men and women aged 65–74 years were offered (i) low dose non-contrast computed tomography to detect coronary artery calcification (CAC) and aortic/iliac aneurysms; (ii) detection of atrial fibrillation (AF); (iii) brachial and ankle blood pressure measurements; and (iv) blood levels of cholesterol and hemoglobin A1c. Web based self booking and data management was used to reduce the administrative burden. Results: Attendance rates were 64.9% ( n  = 678) and 63.0% ( n  = 640) for men and women, respectively. In total, 39.7% received a recommendation for medical preventive actions. Prevalence of aneurysms was 12.4% (95% confidence interval [CI] 9.9–14.9) in men and 1.1% (95% CI 0.3–1.9) in women, respectively ( p  < .001). A CAC score > 400 was found in 37.8% of men and 11.3% of women ( p  < .001), along with a significant increase in median CAC score with age ( p  = .03). Peripheral arterial disease was more prevalent in men (18.8%, 95% CI 15.8–21.8) than in women (11.2%, 95% CI 8.7–13.6). No significant differences between the sexes were found with regard to newly discovered AF (men 1.3%, women 0.5%), potential hypertension (men 9.7%, women 11.5%), hypercholesterolemia (men 0.9%, women 1.1%) or diabetes mellitus (men 2.1%, women 1.3%). Conclusion: Owing to the higher prevalence of severe conditions, such as aneurysms and CAC ≥ 400, screening for CVD seemed more prudent in men than women. The attendance rates were acceptable compared with other screening programs and the logistical structure of the screening program proved successful.